Prevalence of herbal medicine use for maternal conditions in Tanzania: a systematic review and meta-analysis - Japhari, Hamisi S.; Rumisha, Susan F.; Nkoma, Jackline D.; Peter, Emanuel L. (Frontiers in Pharmacology, 2025)
BackgroundStudies reported the prevalence of herbal medicines used for various maternal conditions across regions in Tanzanian communities. However, the lack of a national estimate of herbal medicine use makes it challenging for policymakers, herbal medicine regulators, and healthcare practitioners to make informed decisions on herbal medicine-related policies and practices to optimize their contribution to maternal healthcare. This systematic review and meta-analysis synthesized the national prevalence of herbal medicine use for maternal conditions based on ethnomedical studies conducted in Tanzania.MethodsAuthors systematically searched for published articles in PubMed, Embase, CINAHL, African Index Medicus, and Scopus databases from inception to 29 June 2025. Grey literature was obtained from Google, Google Scholar, OpenGrey, and ProQuest Dissertations & Theses. Articles published in the English language were retrieved. Later, two authors independently assessed the retrieved articles for eligibility and risk of bias using pre-determined criteria. We used the Cochran Q statistics and I2 tests to assess heterogeneity. Also, we applied the random-effects model to determine the pooled prevalence. Finally, subgroup and meta-regression analyses were performed to explore the source of heterogeneity.ResultsAbout 22 studies with 5,248 women from 16 administrative regions of Tanzania were included in a narrative synthesis. These studies had a low to moderate risk of bias. Furthermore, fourteen studies (n = 4,817) were included in the meta-analysis. Overall, the average prevalence of herbal medicine use for maternal conditions was 46% [95%, CI: 34–58], I2 = 93.93%]. Similarly, the commonly managed maternal condition was labor induction 69% [95%, CI: 42–96], and its frequency of citation was (38%).ConclusionThe findings suggest that at least two of every five Tanzanian women are using herbal medicines. However, these findings could understate the national prevalence due to the inadequate availability of data from other regions. The prevalence of herbal medicine (46%) underscores the need for policymakers and healthcare practitioners to account for herbal medicine use while planning for maternal care. To achieve a robust generalizable estimate, data from better-designed ethnomedical surveys from all regions are still needed.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023410082, identifier CRD42023410082.